Infectious mononucleosis is associated with an increased incidence of multiple sclerosis: Results from a cohort study of 32,116 outpatients in Germany - Loosen, Sven H.; Doege, Corinna; Meuth, Sven G.; Luedde, Tom; Kostev, Karel; Roderburg, Christoph (Frontiers in Immunology, 2022)
Background: The pathogenesis of multiple sclerosis (MS) has not yet been fully uncovered. There is increasing evidence that Epstein-Barr-Virus (EBV) infection, which affects over 90% of people during life and causes infectious mononucleosis, leads to an increased incidence of MS, and thus may play a crucial role in the pathophysiology of the disease. Methods: Using the Disease Analyzer database (IQVIA) featuring diagnoses as well as basic medical and demographic data of outpatients from general practices in Germany, we identified a total of 16,058 patients with infectious mononucleosis that were matched to a cohort of equal size without infectious mononucleosis based on patients’ age, sex, index year and yearly consultation frequency. Incidence of MS was compared within a 10-year follow-up period. Results: Within 10 years from the index date, the incidence of MS was 22.6 cases per 100,000 person-years among patient with infectious mononucleosis but only 11.9 cases per 100,000 person-years among individuals without infectious mononucleosis. In regression analysis, infectious mononucleosis was significantly associated with the incidence of MS (HR: 1.86, 95% CI: 1.09-3.16). Subgroup analysis revealed the strongest association between infectious mononucleosis and MS in the age group between 14 and 20 years (HR: 3.52, 95% CI: 1.00-12.37) as well as a stronger association in men compared to women. Conclusion: Infectious mononucleosis is associated with an increased incidence of MS especially in younger individuals. Our data support the growing evidence of a decisive involvement of EBV in the currently unknown pathophysiology of MS and should trigger further research efforts to better understand and potentially prevent cases of this disabling disease in future.